Tuber yield and quality of potato chips as affected by mulch, variety, and potash levels under western Terai, Nepal - Dhakal, R; Sah, SK; Shakya, SM; Basnet, KB (Agronomy Journal of Nepal, 2013)
An experiment was conducted at Divyapuri of Nawalparasi district in the western Terai during winter season 2008/09. There were 16 treatments consisting of two mulch levels (mulched and no mulch) as main plot, two varieties (Kufri Chipsona-1 and Kufri Chipsona-2) as sub plot and four levels of potash (0, 50, 100 and 150 kg K2O /ha) as sub-sub plot arranged in split-split plot design with four replications to evaluate the effect of these treatments on tuber production and their effect on quality of potato chips. The result showed that plant height, number of shoot per plant, dry matter accumulation, number and weight of tuber per plant and tuber yield were significantly higher in Kufri Chipsona-2 than in Kufri Chipsona-1. Lower reducing sugar and browning percent of chips and higher dry matter content and chips recovery were also recorded in Kufri Chipsona-2 compared to Kufri Chipsona-1. Simple economic analysis on gross return, net return and B/C ratio were higher in Kufri Chipsona-2. However, increasing levels of potash from 0-150 kg K2O /ha increased the dry matter accumulation, LAI, number and weight of tuber per plant. The result also showed that as the level of potash increased there was a decrease level of reducing sugar and browning of chips as well. On the other hand, higher potash levels increased the percentage of fat content and recovery of chips. Also increase in potash levels resulted to increase in gross return, net return, and B/C ratio. There was no effect of mulching levels on tuber yield and quality of chips recovery. Of the two varieties, Kufri Chipsona-2 with 100 kg K2O/ha was found suitable for tuber production and recovery of chips quality. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7527 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.121-132